Impact of Foreign Exchange Policy Regime on The Nigerian Construction Sector - Najimu Saka; Dorcas Titilayo Moyanga (Yayasan Riset dan Pengembangan Intelektual, 2023)
In any developing economy, Foreign Exchange Policy Regime FEPR play a critical role in the viability of all sectors of the economy. In Nigeria, the economy is highly dependent on foreign inputs from contracting services, technology, materials, expatriates, etc. Therefore, this study investigated the impact of FEPR on the performance of the Nigerian Construction Sector NCS. To achieve this goal, time series data was extracted from the United Nations Statistic Department UNSD on the NCS, Gross Domestic Product GDP and FEPR for 50 years spanning from 1970 to 2019. The study uses econometric approach including tests of stationarity and co-integration as well as the Generalized Method of Moment GMM to model the relationships between the variables. The study reveals that the 1986 FEPR reform had significant and negative effect on the Nigerian Construction Sector output. This implies that the performance of the construction sector is more dependent on the state of the economy and government policy. Hence, this study recommends urgent diversification of the foreign exchange earnings to moderate the effects of external shocks from oil exports and eliminate misalignment of appropriate FEPR. Finally, government should implement policy on construction local content development to reduce the effect of FER volatility on the NCS.